Quantitative evaluation of diaphragmatic motion during forced breathing in chronic obstructive pulmonary disease patients using dynamic chest radiography - Chen, Jianghong; Zhong, Zhaohui; Wang, Wei; Yu, Ganggang; Zhang, Tingting; Wang, Zhenchang (Frontiers in Integrative Neuroscience, 2022)
Objective: To quantitatively evaluate the bilateral diaphragmatic motion difference during forced breathing between chronic obstructive pulmonary disease (COPD) patients and healthy individuals using dynamic chest radiography technique. Methods: This prospective study included the COPD patients (n: 96, f/m: 17/79, age: 66±8 years old) and healthy individuals (n: 50, f/m: 42/8, age: 53±5 years old) that underwent dynamic chest radiography with a flat panel X-ray detector system during forced breathing in a standing position. After analyzing the excursions, duration and velocity of diaphragmatic motion were automatically calculated using the postprocessing software. The parameters of diaphragmatic motion including excursion, duration, velocity, inhalation/exhalation times were assessed in all subjects for both diaphragms. The correlation between lung function parameters and diaphragmatic motion excursions were further evaluated. Results: The excursions of diaphragmatic motion in COPD patients were significantly decreased in COPD patients compared with healthy individuals during forced breathing (P<0.05). The excursion in COPD patients was 35.93±13.07 mm versus 41.49±12.07 mm in healthy individuals in the left diaphragm, and 32.05±12.29 mm in COPD patients versus 36.88±10.96 mm in healthy individuals in the right diaphragm. The duration of diaphragmatic motion significantly decreased in COPD patients, compared with the healthy individuals (P<0.05). The inhalation time in COPD patients was 2.03±1.19 s versus 2.53±0.83 s in healthy individuals in the left diaphragm and 1.94±1.32 s in COPD patients versus 2.23±1.21 s in healthy individuals in the right diaphragm. The exhalation time was 4.77±1.32 s in COPD patients versus 6.40±2.73 s in healthy individuals in the left diaphragm and 4.94±3.30 s in COPD patients versus 6.72±2.58 s in healthy individuals in the right diaphragm. The peak velocity of diaphragmatic motion showed no significant difference between COPD and healthy groups. The excursions of bilateral diaphragmatic motion showed moderate correlation with FEV1/FVC (r=0.44, P<0.001). Multi-linear regression analysis showed that the excursions of bilateral diaphragm are significantly associated with COPD occurrence (P<0.05). Conclusion: The excursions and duration of diaphragmatic motion during forced breathing are significantly decreased in COPD patients, compared with healthy individuals. Our study showed that precise bilateral diaphragmatic motion activity can be evaluated by dynamic chest radiography.